1969
DOI: 10.1177/030098586900600602
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Neuraxial Edema in Hereford Calves

Abstract: Twelve newborn Hereford calves from 8 herds showed extensor spasms upon stimulation and inability to rise. Neuraxial lesions consisted of widespread vacuolation interpreted as edema and seen chiefly in terminal portions of myelinated bundles and in gray substance containing heavily myelinated fibers. Genetic analysis of 2 of these herds indicated an autosomal recessive pattern of transmission tracing back to a single bull. The identity of the disease in all herds suggested that it had the same hereditary basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The shaker calf syndrome of horned Herefords (Rousseau et a1 1983, neuraxial oedema of polled Hereford calves (Cordy, Richards and Stormont 1969) and spongiform leucoencephalopathy of the silkie terrier (Richards and Kakulas 1978) are clinically most similar to the colt described in this report, but are histologically different. Shaker calves have congenital tremors of the head and body, a wobbly, spastic gait and aphonia, but histologically, neurofilamentous neuronal degeneration occurs in multiple cell groups within the central nervous system and in ganglion cells of the peripheral and autonomic nervous system.…”
Section: Discussionsupporting
confidence: 49%
“…The shaker calf syndrome of horned Herefords (Rousseau et a1 1983, neuraxial oedema of polled Hereford calves (Cordy, Richards and Stormont 1969) and spongiform leucoencephalopathy of the silkie terrier (Richards and Kakulas 1978) are clinically most similar to the colt described in this report, but are histologically different. Shaker calves have congenital tremors of the head and body, a wobbly, spastic gait and aphonia, but histologically, neurofilamentous neuronal degeneration occurs in multiple cell groups within the central nervous system and in ganglion cells of the peripheral and autonomic nervous system.…”
Section: Discussionsupporting
confidence: 49%
“…It has been suggested that this condition is analogous to maple syrup urine disease in children,I3 and it is probably inherited by an autosomal recessive gene. 8 No biochemical abnormality or genetic pattern has been reported in the canine or feline cases.…”
mentioning
confidence: 99%
“…It is probable that the accumulation of fluid in the extracellular spaces, including the lamellae of formed or partly-formed myelin sheaths, is responsible for both interference with myelination and demyelination. This may not be the whole explanation as in hereditary neuraxial edema in Hereford calves (Cordy et al, 1969), myelination was relatively normal despite oedema of white matter.…”
Section: Brain Water Contentmentioning
confidence: 93%